2014
DOI: 10.1093/humrep/deu266
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response prediction in GnRH antagonist treatment for IVF using anti-Müllerian hormone

Abstract: www.clinicaltrials.gov, Protocol ID 13-109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 37 publications
5
48
1
3
Order By: Relevance
“…However, with considering a greater area under curve for no response compared to poor response and the lower number of false positives for no ovarian response, the probability of an individual with AMH level less than 1.2 being in the no response class was higher than being in poor response class. It should be noted that different categories have been presented for the ovarian reserve in various studies all of which are similar [29,31], also the estimated areas under the ROC curves in this study are better compared to the past and recent studies and indicates better accuracy of estimates in this study [26,32]. It should also be noted that in this study, the positive diagnostic likelihood ratios, which were related to former and latter likelihood of developing the disease, were numbers greater than 1 and along with the other reported add values in Table 3, encourage the physicians to use AMH levels for predicting ovarian response in women with infertility problems.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, with considering a greater area under curve for no response compared to poor response and the lower number of false positives for no ovarian response, the probability of an individual with AMH level less than 1.2 being in the no response class was higher than being in poor response class. It should be noted that different categories have been presented for the ovarian reserve in various studies all of which are similar [29,31], also the estimated areas under the ROC curves in this study are better compared to the past and recent studies and indicates better accuracy of estimates in this study [26,32]. It should also be noted that in this study, the positive diagnostic likelihood ratios, which were related to former and latter likelihood of developing the disease, were numbers greater than 1 and along with the other reported add values in Table 3, encourage the physicians to use AMH levels for predicting ovarian response in women with infertility problems.…”
Section: Discussionsupporting
confidence: 50%
“…2 The AUC of ROC and optimal cut-off points for AMH levels with different ovarian responses use of this indicator for predicting ovarian reserve prior to IVF is suggested. However, although the ability of this indicator to predict has been reported much better than basal FSH [10], the predictive value of AMH is higher and the unique characteristics of this indicator make the use of this marker for clinical use more logical [26]. In this study, the successful pregnancy rate was approximately 31 % and a negative relationship was observed between age and number of embryos.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…AMH shows less intra-individual fluctuation than AFC and basal FSH levels, and might be a better, cycle-independent parameter in assessing the ovarian reserve (Van Disseldorp et al , 2010; Verhagen et al ., 2008; La Marca & Volpe, 2006; La Marca et al , 2013); however, AMH levels may decrease if measured during COS (Hamdine et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Our findings was different from other studies which had shown that AMH is the good predictor of ovarian response in GnRH antagonist cycles, but according to our results AFC was found to be a better predictor of ovarian response in patients undergoing GnRH antagonist cycle for having abnormal ovarian reserve. [15][16][17][18][19] A study done among the Vietnamese women had also shown AMH as the best predictor of ovarian response in GnRH antagonist cycle. 20 In the present study we found that the combination of biomarker particularly AFC+AMH was found to have statistical significant association in predicting the ovarian response, whereas the other biomarker combinations like AFC+FSH and AMH+FSH did not had a significant association in the ovarian response prediction.…”
Section: Discussionmentioning
confidence: 99%